SAMPURAGA: PENCIPTAAN OPERA BATAK - Enrico Alamo (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2014)
Opera Batak Sampuraga is a play that began from the experience of seeing the site Sampuraga Hot Spring, located in the area Sirambas Mandailing-Natal, and stories  are  told  from  mouth to  mouth  (oral  literature).  Then  rearrangement  is done regarding characterization and the occuring event by using some structures of  Indonesian  modern  theater.  As  Batak  Opera  has  some  similarities  with  the structure of Indonesian modern theater, Opera Batak Sampuraga as an object of art  creation,  experiences  a  touch  of  creativity  with  the  presence  of  various elements of art from other regions; one of them is gundala-gundala, a traditional theater  of  Karo  region.  Sampuraga  play  is  a  human  obsession  and  ambition  in reaching  their  goals,  which  requires  sacrifice,  although  it  eventually  leads  a curse.  Opera  This  play  is  presented  through  a  realism  approach  with representation  style.  The  form  of  tragedy  is  chosen  because  of  the  incident happening  to  two  human  beings;  mother  and  child.  This  creation  is  important because  Opera  Batak  Sampuraga  is  similar  to  the  pattern  and  characterization of plays in Indonesian modern theater.